2012
DOI: 10.1016/j.juro.2012.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Durability of the Distal Urethral Polypropylene Sling for the Treatment of Stress Urinary Incontinence: Minimum 11-Year Followup

Abstract: The distal urethral polypropylene sling procedure has excellent long-term durability in the treatment of stress urinary incontinence, in addition to low morbidity and low cost as previously described. Eleven years after the procedure the majority of patients report symptom improvement. Nevertheless, many older patients are unable to participate in followup. When choosing an anti-incontinence procedure, durability should be considered in light of patient age given that the theoretical advantages of long-term du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Several surgical techniques have been used historically, but mesh slings have gained worldwide acceptance since it is highly effective, technically easy and with low complication rates. The TO sling technique has high success rates whereas offering low complications rates ( 7 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surgical techniques have been used historically, but mesh slings have gained worldwide acceptance since it is highly effective, technically easy and with low complication rates. The TO sling technique has high success rates whereas offering low complications rates ( 7 , 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cure rates after sling surgery vary in the literature from 70 to 100% and are influenced by several factors such as technique modifications, incontinence severity, parity, surgeon's experience, diversity of patients and subjective criteria, which make it difficult to compare results ( 6 ). With polypropylene slings, a 80% efficiency rate in the first five years and 63% after 11 years of follow-up have been demonstrated ( 13 ). For TO slings, Sivasglioglu et al have demonstrated a cure rate of 85% after five years of follow-up ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different practitioners may keep TVT patients overnight, thus skewing some of the cost assumptions. Another potential limitation with respect to the analysis lies with practitioners who use their own hand‐cut mesh to create a TVT ; this would decrease the cost of the TVT device to below that of the base‐case analysis considered in this study. This variation in cost was addressed with the one‐way sensitivity analysis reported above.…”
Section: Discussionmentioning
confidence: 99%
“…103 The midurethral sling is the most studied procedure for SUI, and many studies have shown durability, efficacy, and improvement of quality of life. 104 Although uncommon, when mesh complications such as urinary tract erosion occur or when chronic pain develops, these side effects can be difficult to manage.…”
Section: Prevention and Therapeutic Strategies For Lut Dysfunctionmentioning
confidence: 99%